Environmental risk measurement on mount site growth in Aqaba, Jordan: Recommendations on management system - Tarrad, M.; Al Omari, Omar; Al-Fugara, A.; Al-Rwashdeh, M. (INSInet Publications, 2011)
Aqaba is one of the main cities in Jordan which has ridged and surrounding hilly geography. Construction activities in these areas are increasing gradually, above all for housing and commercial purposes. Such express development put the environment at risk by natural ruins such as flood, changes of climate, landslides and so on, and becomes a safety hazard to the life and assets of local residents. Developing a management system at an early Stage can decrease the past effect of any environmental risk due to the intense construction. This paper identifies the surrounding hills of Aqaba which are exposed to the risk that we mean, and presents mainly a management system at an early Stage starting from geotechnical analysis. Measurement is made by ranking system, and is reviewed as matrices. The ranking systems are shaped after alteration from other obtainable strategies and requirements. Some assessment procedures and proposals for weak point's improvement in the reports are also discussed. Outcomes from the evaluations are also revealed in environmental threat map by means of Geographical Information System (GIS) to discover high, moderate or low possibility areas.